Strengthening the information deficit model for disaster preparedness: Mediating and moderating effects of community participation. (June 2020) - Abunyewah, Matthew; Gajendran, Thayaparan; Maund, Kim; Okyere, Seth Asare
Abstract: The information deficit model (IDM) suggests that disseminating relevant information to the public about an issue or concern can result in people changing their perception, beliefs and attitude leading to positive actions. In the context of disaster preparedness, IDM suggests that providing information associated to disaster risk and response actions to concerned stakeholders should increase the level of disaster preparedness, leading to mitigation in the growing damages caused by disasters. Yet, in spite of notable global and local strategy of disaster education and information campaigns, there has not been a commensurate success in flood preparedness worldwide. Based on a field study in three flood-prone informal communities of Accra, Ghana, this paper examines the role of community participation in improving the effectiveness of the IDM towards disaster preparedness. By using Structural Equation Modelling (SEM), this paper develops a model to test the mediating and moderating effects of 'community participation' on the relationship between 'information sufficiency' and 'intentions to prepare'. Results showed that disaster information that is accessible, comprehensive, and tailored to the needs of the public, strongly influences intentions to prepare for disasters. However, this effect occurs when community participation is integrated into the information dissemination process of disaster risks. Thus, if disaster preparedness is to be realised, disaster management programs/activities must ensure sufficient and participatory information dissemination as a measure to influence intentions to prepare for disaster risks among the general public.